51Cr-Bleomycin, a New Oncophilic Radiopharmaceutical I. Activity Concentrations in Transplantable Tumours and Organs-Tissues of Mice - Rembelska, Maria J.; Liniecki, J. (Nuklearmedizin - NuclearMedicine, 1982)
A method was developed for labelling bleomycin with 51Cr. The complex was administered to mice (Swiss and C57-B1/6) bearing 5 transplantable tumours: Ehrlich ascites tumour, NK/Ly lymphoma, Lewis lung carcinoma, melanoma B-16, and Sarcoma 180. Activity concentration in neoplasms, blood and numerous organs was determined 12, 24 and 48 hrs after injection. An identical procedure was applied using 58Co-bleomycin as a reference oncophilic substance. Tumour/ non-tumor ratios exceeding substantially unity were found for blood, muscle and bone indicating preferential accumulation of both 58Co and 51Cr in all the neoplasms tested. The ratios were lower (by a factor 2–3) for 51Cr than for 58Co; however, it is postulated that the gamma-quantum energy of 51Cr which is higher than that of the commonly used 57Co, should offset to some degree this difference when scintigraphic tumour detection in a patient is to be attempted. In conclusion, clinical trials with 51Cr-bleomycin, which is cheaper than its 57Co-counterpart, appear warranted.